Rancang bangun sistem monitoring dan kontrol pH air untuk budidaya ikan lele - Ari Rahayuningtyas; Diang Sagita; Novita Dwi Susanti (AGROINTEK, 2023)
One of the water quality parameters that are important to consider in fish farming is pH. Unstable pH conditions can cause a decrease in water quality and cause fish to harvest less than optimal yields. Under certain conditions, there is an extreme change in the pH value, so it needs to be normalized again. This study aims to design a monitoring and control system of pH for catfish farming. The control system consisted of an SKU SEN0161 type pH sensor, equipped with two pumps to automatically flow alkaline and acidic pH solutions. The design method used was the prototyping method, i.e. Listen to Customer (Design criteria collection), Design and Build Prototype, and Test Drive and Evaluation. Based on the static characteristic test on the pH sensor, it was found that the pH sensor reading error was 0.11 with a deviation of 0.03. A small error value indicates that the sensor has high accuracy and a little deviation value indicates that the sensor has a high level of precision. For the repeatability test with an interval measurement of 5 minutes, the sensor measurement had a deviation of 0.01. The performance test of the pH control system showed that the system had been able to control the pH according to the set point (6 and 7.5), both under acidic conditions (pH 5.4) and under alkaline conditions (pH 8). The system had also been able to store and display data on Android devices in real-time (24 hours non-stop) via an internet connection, making it easier to monitor by users. It was also found that catfish can grow well at pH 6.5-8.